Effect of a Perioperative Hypotension-Avoidance Strategy Versus a Hypertension-Avoidance Strategy on the Risk of Acute Kidney Injury: A Clinical Research Protocol for a Substudy of the POISE-3 Randomized Clinical Trial. (January 2022) - Garg, Amit X.; Cuerden, Meaghan; Aguado, Hector; Amir, Mohammed; Belley-Cote, Emilie P.; Bhatt, Keyur; Biccard, Bruce M.; Borges, Flavia K.; Chan, Matthew; Conen, David; Duceppe, Emmanuelle; Efremov, Sergey; et al.
Background: Most patients who take antihypertensive medications continue taking them on the morning of surgery and during the perioperative period. However, growing evidence suggests this practice may contribute to perioperative hypotension and a higher risk of complications. This protocol describes an acute kidney injury substudy of the Perioperative Ischemic Evaluation-3 (POISE-3) trial, which is testing the effect of a perioperative hypotension-avoidance strategy versus a hypertension-avoidance strategy in patients undergoing noncardiac surgery. Objective: To conduct a substudy of POISE-3 to determine whether a perioperative hypotension-avoidance strategy reduces the risk of acute kidney injury compared with a hypertension-avoidance strategy. Design: Randomized clinical trial with 1:1 randomization to the intervention (a perioperative hypotension-avoidance strategy) or control (a hypertension-avoidance strategy). Intervention: If the presurgery systolic blood pressure (SBP) is <130 mmHg, all antihypertensive medications are withheld on the morning of surgery. If the SBP is ≥130 mmHg, some medications (but not angiotensin receptor blockers [ACEIs], angiotensin receptor blockers [ARBs], or renin inhibitors) may be continued in a stepwise manner. During surgery, the patients' mean arterial pressure (MAP) is maintained at ≥80 mmHg. During the first 48 hours after surgery, some antihypertensive medications (but not ACEIs, ARBs, or renin inhibitors) may be restarted in a stepwise manner if the SBP is ≥130 mmHg. Control: Patients receive their usual antihypertensive medications before and after surgery. The patients' MAP is maintained at ≥60 mmHg from anesthetic induction until the end of surgery. Setting: Recruitment from 108 centers in 22 countries from 2018 to 2021. Patients: Patients ( 6800) aged ≥45 years having noncardiac surgery who have or are at risk of atherosclerotic disease and who routinely take antihypertensive medications. Measurements: The primary outcome of the substudy is postoperative acute kidney injury, defined as an increase in serum creatinine concentration of either ≥26.5 μmol/L (≥0.3 mg/dL) within 48 hours of randomization or ≥50% within 7 days of randomization. Methods: The primary analysis (intention-to-treat) will examine the relative risk and 95% confidence interval of acute kidney injury in the intervention versus control group. We will repeat the primary analysis using alternative definitions of acute kidney injury and examine effect modification by preexisting chronic kidney disease, defined as a prerandomization estimated glomerular filtration rate <60 mL/min/1.73 m 2 . Results: Substudy results will be analyzed in 2022. Limitations: It is not possible to mask patients or providers to the intervention; however, objective measures will be used to assess acute kidney injury. Conclusions: This substudy will provide generalizable estimates of the effect of a perioperative hypotension-avoidance strategy on the risk of acute kidney injury.